Somatic embryogenesis in Abies alba Mill - Salaj, Terezia; Panis, Bart; Swennen, Rony; Klubicová, Katarina (2023)
COPYTREE: INNOVATIVE WOODY PLANT CLONING FIRST CONFERENCE OF COST ACTION CA21157 17 & 18 April 2023 Faculty of Chemistry (USC) Santiago de Compostela, SPAIN